Comparative analysis of HKT genes in Ipomoea pes-caprae unveils conserved Na+/K+ symporter functions within the gene family - Zhonghua Guo; Zhonghua Guo; Jin Sun; Jin Sun; Xingguang Chen; Hui Li; Sisi Liang; Fengying Liu; Tong Qu; Huaer Wang; Xueli Li; Zitong Ou; et al. (Frontiers in Plant Science)
The HKT protein family plays a vital role in plant responses to salt stress by mediating sodium (Na+) and potassium (K+) transport and maintaining Na+-K+ balance. Ipomoea pes-caprae (IPC), a pantropical creeping plant distributed along coastal regions in tropical and subtropical zones, exhibits exceptional salt tolerance. Understanding its salt tolerance mechanisms provides valuable insights for developing salt-tolerant crops and identifying candidate genes for genetic engineering. In this study, we identified two HKT genes, IpcHKT1;1 and IpcHKT1;2, in IPC. Phylogenetic analysis with HKT genes from other Ipomoea species revealed that all analyzed species contain two HKT genes located adjacently on the same chromosome. Comparative analysis of conserved motifs and intron-exon structures indicated that, despite their close evolutionary relationship, the HKT genes in IPC may exhibit functional divergence. Promoter analysis showed that their regulatory regions are enriched with cis-elements associated with responses to biotic and abiotic stresses, hormonal signaling, and growth, highlighting functional diversity within the HKT family. Subcellular localization experiments demonstrated that IpcHKT1;1 and IpcHKT1;2 are ion transporters localized to the plasma membrane. Heterologous expression in yeast confirmed their role in Na+/K+ symporter. Furthermore, RT-qPCR analysis revealed distinct expression patterns under salt stress: IpcHKT1;2 was significantly upregulated in roots, while IpcHKT1;1 expression was transitionally downregulated at 400 mM NaCl treatment. Prolonged high expression of IpcHKT1;2 in roots suggests its critical role in sustained salt stress tolerance. These findings provide new insights into the molecular mechanisms of salt tolerance in IPC. The identification of IpcHKT1;1 and IpcHKT1;2 as key players in salt stress responses offers promising genetic resources for enhancing crop resilience to soil salinity, addressing challenges associated with global salinization.